2011
DOI: 10.1111/j.1537-2995.2011.03297.x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of RHD alleles in Argentineans with variant D phenotypes

Abstract: The D phenotype distribution in G2 resembles that in Europeans while the frequencies in G1 account for the Amerindian and African genetic contribution. The genotyping strategy described here is suitable to study D variants in the overall population and could allow a better use of the few available D- units and a rational administration of anti-D immunoprophylaxis. The results also show that weak D Type 1 alleles do not exclusively segregate with a Ce allele, as assumed until present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
1
13
1
1
Order By: Relevance
“…However, the optimal application of DNA typing requires an exhaustive analysis of the polymorphisms and allele distribution of the blood group genes under study, in particular of the RH system, since a high level of genetic variability was observed in this system among different ethnic groups . In a previous study, we analyzed the RHD allele pool responsible for altered D antigen expression and determined the frequency of the D– phenotype in the overall Argentinean population, which was 7.2% . In this work we examined the RHD locus in routine serologically D– individuals of this admixed population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the optimal application of DNA typing requires an exhaustive analysis of the polymorphisms and allele distribution of the blood group genes under study, in particular of the RH system, since a high level of genetic variability was observed in this system among different ethnic groups . In a previous study, we analyzed the RHD allele pool responsible for altered D antigen expression and determined the frequency of the D– phenotype in the overall Argentinean population, which was 7.2% . In this work we examined the RHD locus in routine serologically D– individuals of this admixed population.…”
Section: Discussionmentioning
confidence: 99%
“…The rest of the D–/ RHD + samples were subjected to an RHD exon scanning procedure based on PCR‐SSP to analyze multiple RHD exon polymorphisms . When RHD Exons 3 to 7 were not amplified, the RHD‐CE‐D s allele was investigated by a specific PCR that amplifies a 5′RHD‐RHCE3′ hybrid Exon 3 characteristic of the Type 1 variant .…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports have already described other methods and strategies to identify D variants and laboratory‐developed tests are still a good option . Besides that, commercial kits are also available, from kits based on sequence‐specific primers PCR that covers a limited numbers of D variants to high‐throughput methods, as microarrays 10,12‐14…”
Section: Benefits Of the Molecular Approachmentioning
confidence: 99%
“…Genomic DNA was isolated from peripheral blood with a commercially available purification kit (ADN PuriPrep‐S, INBIO Highway). Most common weak D and partial D alleles were investigated by allele‐specific polymerase chain reaction (PCR) techniques . DNA array analysis was performed with the RHD BeadChip platform from BioArray Solutions (Immucor), which uses probes directed to polymorphic sites for many RHD variants .…”
Section: Brief Methodsmentioning
confidence: 99%